An Air Firing Base Metal Resistor and Conductor System for Low Cost Thick Film Circuit Manufacture. (1981) - Browne, E. K.; Walton, B.
Abstract : A series of air-firing base metal resistor pastes which yield resistors with properties comparable to those of conventional precious metal thick film resistors has been developed. The pastes can be post-fired or co-fired with air-firing nickel conductors in a very fast firing cycle thus providing a base metal combination which can be processed using conventional furnaces. This is concluded to be a significant contribution to the manufacture of thick film circuits of low cost especially in view of recent large increases in the prices of precious metals.